2018
DOI: 10.1016/j.tjog.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and prescription patterns of Chinese herbal medicine in clinical practice for the treatment of anemia

Abstract: This study demonstrates that CHM may be applied as an integral element of treatment for patients with anemia. It also provides insight regarding individual therapy and common clinical practices of TCM physicians in the treatment of anemia. Further research is required to explore potential interactions and possible mechanisms at play with CHM management of anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…Traditional Chinese medicine (TCM) plays a unique role in the treatment of many diseases, and a growing body of evidence has shown that TCM is increasingly being used for preventing CKD and anemia [ 13 15 ]. Jian-Pi-Yi-Shen (JPYS), a Chinese herbal formula, is composed of eight medicinal herbs, that is, Astragali Radix, Atractylodis Macrocephalae Rhizoma, Amomi Fructus Rotundus, Dioscoreae Rhizoma, Cistanches Herba, Rhei radix et Rhizoma, Salviae miltiorrhizae Radix et Rhizoma, and Glycyrrhizae radix et Rhizoma Praeparata cum Melle.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) plays a unique role in the treatment of many diseases, and a growing body of evidence has shown that TCM is increasingly being used for preventing CKD and anemia [ 13 15 ]. Jian-Pi-Yi-Shen (JPYS), a Chinese herbal formula, is composed of eight medicinal herbs, that is, Astragali Radix, Atractylodis Macrocephalae Rhizoma, Amomi Fructus Rotundus, Dioscoreae Rhizoma, Cistanches Herba, Rhei radix et Rhizoma, Salviae miltiorrhizae Radix et Rhizoma, and Glycyrrhizae radix et Rhizoma Praeparata cum Melle.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese herbal medicine (CHM) has been widely used to treat anemia (Bradley et al, 1999;Chen et al, 2018). According to Traditional Chinese Medicine (TCM) theory, blood deficiency is the main feature of anemia and spleen and kidney deficiencies are the basic pathological features.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) plays a unique role in the treatment of many diseases, and a growing body of evidence has shown that TCM is increasingly being used for preventing CKD and anemia [8][9][10]. Jian-Pi-Yi-Shen improved the anemia symptoms by increasing the serum EPO level and hypoxia inducible factor (HIF)-α protein in 5/6 nephretomized rats [11,12].…”
Section: Introductionmentioning
confidence: 99%